PEMBERDAYAAN KELOMPOK PEREMPUAN DAN ANAK UNTUK KESEHATAN REPRODUKSI KELUARGA DIKECAMATAN MONTASIK KABUPATEN ACEH BESAR - Gani, Shella Widya; Zuhkrina, Yuli; Yolanda; Zulaikha; Amalia, Shinta; Andriyani, Cut Novi (Transpublika Publisher, 2021)
Women's empowerment is a process of awareness and capacity building for greater participation, greater power and oversight of decision-making and transformational action in order to produce greater equality between women and men. Empowerment of women is an important strategy in increasing the role of women in increasing their potential so that they are more capable of being independent and working. Reproductive health is a state of complete physical, mental and social well-being, which is not merely free from disease or disability, in all matters relating to the reproductive system, as well as its functions and processes. Based on data from the World Health Organization 2010 (WHO), poor women's reproductive health problems have reached 33% of the total burden of disease suffered by women in the world, one of which is vaginal discharge. The number of women in the world who have experienced vaginal discharge is 75%, while European women who experience vaginal discharge are 25%. This figure is greater than reproductive problems in men which only reached 12.3% at the same age as women. These data show that vaginal discharge in women in the world, Europe, and in Indonesia is quite high. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge of reproductive health which was in the good category as many as 33 (70.2%). In conclusion, there is a significant increase in respondents' knowledge after being given counseling.